Partisipasi Masyarakat dalam Mitigasi Kebakaran Hutan dan Lahan di Kecamatan Landasan Ulin - Ahmad Naufal Setiyawan; Rosalina Kumalawati; Muhammad Efendi; Ellyn Normelani (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze community participation in forest and land fire mitigation efforts in Landasan Ulin District. The findings are expected to provide an empirical overview of the dynamics of socio-culturally based participation, thereby facilitating the formulation of mitigation strategies that are effective, participatory, and sustainable. A descriptive quantitative research method was employed. The study population comprised the entire population of Landasan Ulin District (84,978 people), with a sample of 108 respondents selected using stratified random sampling. The results indicate that all respondents (108 individuals) were aware of forest and land fires, with social media serving as the primary source of information (cited by 54 respondents). A total of 99 respondents experienced direct impacts, such as haze, respiratory issues, and environmental pollution. However, community participation in prevention and response activities remained low; only 49 respondents had participated, with activities primarily consisting of *gotong royong* (communal cooperation) for land clearing. Regarding mitigation effort categories, 10 respondents (9.26%) fell into the high category, 58 (53.70%) into the medium category, and 44 (40.74%) into the low category. Overall, the number of community members in the low mitigation category significantly exceeded those in the high category.